DIGITAL RESILIENCE IS THE NEW NORMAL OF HIGHER EDUCATION: STUDENT AND TEACHER PERCEPTIONS FROM ROMANIA - IACOB, Laura; PARVU, Iuliana; CHIRU, Claudiu (Annals of Spiru Haret University. Economic Series, 2024)
This paper aims to emphasize the fact that digital technologies in higher education are a necessity, both teachers and students must develop their ability to adapt and deal with informational technology challenges. Data collection was carried out through the administration of two online questionnaires, addressed both to students and teachers from the Faculty of Law and Economics, Spiru Haret University, in December 2021. The students shared their personal experience regarding distance learning in relation to the classical system (in classroom). Second questionnaire measures the frequency of teaching-learning methods, the ways of organizing the teaching materials existing in the eLearning platform, the media resources, evaluation methods used in teaching activities at distance and perceptions regarding some issues related with eLearning implementation. Based on the results, the authors highlighted that the online education process cannot be achieved through a simple translation of the didactic activity from the classroom to the virtual environment. The preparation of didactic materials for eLearning system requires more time and digital skills and special protection of intellectual property rights. The sanitary crisis accelerated the digitization of education, so that students are already aware of the advantages of E-Learning, but some disadvantages of this system can only be combated through blended learning.